"It's about half and half": Austerity, possibility and daily life inside a depopulated Detroit neighborhood. (September 2018) - Draus, Paul; Roddy, Juliette; McDuffie, Anthony
Highlights: Detroit is often used a representative example of postindustrial urban trends. Ethnographic and economic research provides on-the-ground view. People adapt to shifting neighborhood circumstances in different ways. Perspectives of current residents are examined in light of theoretical debates.